MANAJEMEN PERSEDIAAN BAHAN BAKU DODOL RUMPUT LAUT INDUSTRI â€œCITA RASAKUâ€ KELURAHAN TINGGEDE KECAMATAN MARAWOLA KABUPATEN SIGI - Abd. Mukmin,Arifuddin Lamusa, Sulaeman, Ahmad (AGROTEKBIS, 2015)
The aims of this study are the amount of raw material ordering, amount of supply raw materials and time to do a re-ordering of the raw material supply in Industry "Cita Rasaku". Data analysis tool used in this study are EOQ (Economic Order Quantity), Safety stock and Reorder Point. The results showed that the amount of the economical purchase of seaweed raw materialsby using EOQ analysis of raw material inventory at Cita Industry Rasaku for February to May 2014 are 460.93 kg, 354.56 kg, 419.52 kg, and 454.48 kg.Safety stock that should be always available in the warehouse at Cita Rasaku industry is 50 kg.Reorder point should be done by Cita Rasaku Industry are  59.22 kg in February, 57.09 kg in March, 58.39 kg in April and 59.09 kg in May.